Alcohol misuse, health-related behaviors, and burnout among clinical therapists in China during the early Covid-19 pandemic: A Nationwide survey - Tao, Rui; Hsu, Michael; Min, Kaiyuan; Mo, Daming; Geng, Feng; Xia, Lei; Liu, Tingfang; Liu, Yuanli; Jiang, Feng; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Public Health, 2023)
Objectives: This study aimed to assess the extent of alcohol use and misuse among clinical therapists working in psychiatric hospitals in China during the early COVID-19 Pandemic, and to identify associated factors. Methods: An anonymous nationwide survey was conducted in 41 tertiary psychiatric hospitals. We collected demographic data as well as alcohol use using the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) and burnout using the Maslach Burnout Inventory Human Services Survey. Results: In total, 396 clinical therapists completed the survey, representing 89.0% of all potential participants we targeted. The mean age of participants was 33.8 years old, and more than three-quarters (77.5%) were female. Nearly two-fifths (39.1%) self-reported as current alcohol users. The overall prevalence of alcohol misuse was 6.6%. Nearly one-fifth (19.9%) reported symptoms of burnout with high emotional exhaustion in 46 (11.6%), and high depersonalization in 61 (15.4%). Multiple logistic regression showed alcohol use was associated with male gender (OR =4.392; 95% CI =2.443-7.894), single marital status (OR =1.652; 95% CI =0.970-2.814), smoking habit (OR =3.847; 95%CI =1.160-12.758) and regular exercise (OR =2.719; 95%CI =1.490-4.963). Alcohol misuse was associated with male gender (OR =3.367; 95% CI =1.174-9.655), a lower education level (OR =3.788; 95%CI =1.009-14.224), smoking habit (OR =4.626; 95%CI =1.277-16.754) and high burnout (depersonalization, OR =4.848; 95%CI =1.433-16.406). Conclusions: During the COVID-19 pandemic, clinical therapists’ alcohol consumption did not increase significantly. Male gender, cigarette smoking, and burnout are associated with an increased risk of alcohol misuse among clinical therapists. Targeted intervention is needed when developing strategies to reduce alcohol misuse and improve clinical therapists’ wellness and mental health.